Geometric Anatomy Basis for Safe and Effective Focal Ablation of Prostate Cancer by Irreversible Electroporation (IRE) - Olivier Cussenot; Ruth Macpherson; Tom Leslie; Luca Lunelli; Giancarlo Marra; Marc Laniado; Freddie C. Hamdy; Richard J. Bryant (MDPI AG, 2023)
Irreversible electroporation (IRE) is a recent and minimally invasive method of partial prostate ablation. However, knowledge of the essential landmarks of prostate anatomy is crucial to achieving safe and effective partial ablation by IRE. High-quality imaging of the prostate is essential before the procedure. The individual morphological pattern of the prostate must be taken into account and detailed mapping with measurement of the lesion is necessary to determine optimal needle placement. The entire tumour volume must be covered while ensuring the safety of critical anatomical structures such as the rectum, urethra, nerve bundles and sphincter muscle.